2012
DOI: 10.1080/17439884.2012.685077
|View full text |Cite
|
Sign up to set email alerts
|

A case study of using an online community of practice for teachers’ professional development at a secondary school in China

Abstract: In this case study, an online community was designed at a secondary school in China for the teachers to prepare their lessons collectively, reflect on their teaching practices, collect comments from peers, and share resources. A survey was administered to the teachers to investigate their perceptions on the online community for their professional development. Two hundred and eighty-three teachers responded to the survey and eight teachers were further interviewed by email. The result showed that most teachers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Some researchers (e.g., Cambridge & Perez-Lopez, 2012;Evans & Powell, 2007;Schlager & Fusco, 2003) critique the optimal design, conceptual role and practical use of online CoPs to support educators' decision making, professional development and preservice teacher training. In Asia and other parts of the world, studies have shown that active participation in online CoPs enhances student teachers' critical reflection (Yang, 2009) and knowledge sharing (Tseng & Kuo, 2014); enriches teachers' perspectives on teaching and learning and helps them tackle demanding tasks more effectively through sharing expertise and socializing (Kablian, Adlina, & Embi, 2011;Wang & Lu, 2012); creates a venue for knowledge co-construction and inspiration among student teachers and in-service teachers (Tang & Lam, 2014); and facilitates interpersonal relationship building (Clarke M, 2009), potentially changes pre-service teachers' teaching efficacy (Cheong, 2010) and transforms their perception of teacher identity (Trent & Shroff, 2013).…”
Section: Online Communities Of Practice Learning To Teach and Chinesmentioning
confidence: 98%
“…Some researchers (e.g., Cambridge & Perez-Lopez, 2012;Evans & Powell, 2007;Schlager & Fusco, 2003) critique the optimal design, conceptual role and practical use of online CoPs to support educators' decision making, professional development and preservice teacher training. In Asia and other parts of the world, studies have shown that active participation in online CoPs enhances student teachers' critical reflection (Yang, 2009) and knowledge sharing (Tseng & Kuo, 2014); enriches teachers' perspectives on teaching and learning and helps them tackle demanding tasks more effectively through sharing expertise and socializing (Kablian, Adlina, & Embi, 2011;Wang & Lu, 2012); creates a venue for knowledge co-construction and inspiration among student teachers and in-service teachers (Tang & Lam, 2014); and facilitates interpersonal relationship building (Clarke M, 2009), potentially changes pre-service teachers' teaching efficacy (Cheong, 2010) and transforms their perception of teacher identity (Trent & Shroff, 2013).…”
Section: Online Communities Of Practice Learning To Teach and Chinesmentioning
confidence: 98%
“…When interacting with their peers, teachers are able to effectively reflect on different teaching techniques, choosing to adopt them or not. Thus, professional development programs that promote acquirement of collaborative skills have proven the most effective (WILSON, 2012), creating learning and professional development opportunities (NATiONAL RESEARCH COUNCiL, 2007, WANG;LU, 2012). As stressed by other authors, teacher professional development initiatives may have a limited impact when only a minor fraction of the teachers is reached (EL-HANi; GRECA, 2013).…”
Section: Limitations and Perspectivesmentioning
confidence: 99%
“…international institutions have considered that teacher professional development is a crucial component for general educational achievement improvement (NATiONAL RESEARCH COUNCiL, 2007, OECD, 2010, UNESCO, 2008. in this context, the use of online professional development programs can provide opportunities for learning and collaboration among teachers (DEDEET AL, 2008, BROWN;NEAL, 2013, NATiONAL RESEARCH COUNCiL, 2007, PARK et al, 2007LU, 2012, MARTiNS et al, 2015. Like any online-based program, this particular virtual learning community aims at providing teachers with up-to-date development resources which they can access at their own convenience (DEDE ET AL, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The success of professional development programs is dependent then, not only on the content it covers, but on the processes used for professional development to occur and the context which participants apply their knowledge to (Wang, 2012). Therefore, professional development should be a long -term ongoing process of putting newly -acquired knowledge into practice through teachers' actual practice (Schlager & Fusco, 2004).…”
Section: Professional Developmentmentioning
confidence: 99%